High incidence of neural tube defects in Northern part of India - Rai, Sunil; Singh, Royana; Pandey, Sharad; Singh, Kulwant; Shinde, Neeraj; Rai, Sangita; Prasad, Rajniti; Shama, Satya (Asian Journal of Neurosurgery, 2016)
Background: In the absence of primary care and prevailing associated social stigma, many patients of neural tube defects (NTDs) from remote areas die without getting any treatment. The high number of such untreated cases and unregistered deaths in these areas made us ponders to the fact that tertiary care center-based studies do not represent the true incidence of NTDs. Materials and Methods: We did a population-based survey for NTDs births of rural areas from Jaunpur to Ghazipur district in Eastern Uttar Pradesh. These districts are among the least developed areas of Northern India in Uttar Pradesh among other 17. Results: The data show an incidence of 7.48 per 1000 live births. Conclusion: Besides of unawareness regarding periconceptional folate supplementation, intensive effort is required to design adequately powered studies to search other key factors responsible for high prevalence of NTDs.
Keywords: Epidemiology; India; meningomyelocele; neural tube defect